Der p 1 is the primary activator of Der p 3, Der p 6 and Der p 9 the proteolytic allergens produced by the house dust mite Dermatophagoides pteronyssinus - Herman, Julie; Thelen, Nicolas; Smargiasso, Nicolas; Mailleux, Anne-Catherine; Luxen, André; Cloes, Marie; De Pauw, Edwin; Chevigné, Andy; Galleni, Moreno; Dumez, Marie-Eve (Biochimica et biophysica acta, 2014)
The enzymatic activity of the four proteases found in the house dust mite Dermatophagoides pteronyssinus is involved in the pathogenesis of allergy. Our aim was to elucidate the activation cascade of their corresponding precursor forms and particularly to highlight the interconnection between proteases during this cascade. The cleavage of the four peptides corresponding to the mite zymogen activation sites was studied on the basis of the Förster Resonance Energy Transfer method. The proDer p 6 zymogen was then produced in Pichia pastoris to elucidate its activation mechanism by mite proteases, especially Der p 1. The role of the propeptide in the inhibition of the enzymatic activity of Der p 6 was also examined. Finally, the Der p 1 and Der p 6 proteases were localised via immunolocalisation in D. pteronyssinus. All peptides were specifically cleaved by Der p 1, such as proDer p 6. The propeptide of proDer p 6 inhibited the proteolytic activity of Der p 6, but once cleaved, it was degraded by the protease. The Der p 1 and Der p 6 proteases were both localised to the midgut of the mite. Der p 1 in either its recombinant form or in the natural context of house dust mite extracts specifically cleaves all zymogens, thus establishing its role as a major activator of both mite cysteine and serine proteases. This finding suggests that Der p 1 may be valuable target against mites. •We elicited the activation mechanism of proteases in D. pteronyssinus.•Der p 1 is the major activator of digestive mite cysteine and serine proteases.•Der p 1 (recombinant or natural) cleaves proDer p 1, 3, 6 and probably proDer p 9.•The propeptide inhibits the proteolytic activity of Der p 6.•As Der p 1, Der p 6 chymotrypsin is present in the mite gut.